USING WRITTEN WORK IN DEVELOPING STUDENTS' SPEAKING COMPETENCE - Sharipova Sarvinoz Sayid qizi (Journals Park Publishing, 2024)
This research explores the use of written tasks to enhance the speaking competence of students. While verbal communication is central to language development, written exercises provide a structured way to build the foundational skills necessary for effective speaking. The study focuses on how different forms of written work—such as essays, summaries, and reflective writing—can support learners in organizing their thoughts, expanding vocabulary, and practicing grammatical structures, which are crucial for improving fluency and accuracy in spoken language. Through examining pedagogical methods and practical applications, the research offers insights into integrating writing into language teaching to facilitate better oral communication skills.
Keywords: Speaking competence, written tasks, language development, pedagogical methods, fluency, accuracy, language teaching, oral communication skills.